Aligning authoritarian regionalism: discourses and strategies in the EAEU and BRI - de Archellie, Reynaldo; Arumsari, Chysanti; Atirennu, Puspita (Frontiers in Political Science, 2026)
This article analyzes the strategic convergence of Russia’s Eurasian Economic Union (EAEU) and China’s Belt and Road Initiative (BRI) as manifestations of authoritarian regionalism. Drawing on Obydenkova and Libman’s framework and insights from new regionalism theory, the study examines how these initiatives serve as instruments of geopolitical repositioning and normative resistance to Western liberalism. A comparative discourse analysis of official speeches by Vladimir Putin and Xi Jinping reveals overlapping narratives emphasizing sovereignty, multipolarity, development, and civilizational revival. While Russia highlights strategic autonomy, China promotes connectivity and peace, yet both frame regionalism as a post-Western alternative. The study argues that authoritarian regionalism is not merely regime-protective but actively shapes international norms and regional orders. Limitations include the exclusive focus on elite-level rhetoric and the absence of grassroots or institutional performance analysis. The findings contribute to a broader understanding of non-liberal regionalism in the context of a shifting, multipolar global order.